PENINGKATAN KEMAMPUAN MENYIMAK DONGENG DENGAN MENGGUNAKAN MEDIA AUDIO SISWA KELAS VII.H MTsN MODEL SUNGAI PENUH PROVINSI JAMBI - Ria Agustina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This research was stimulated by lack of students’ ability at the class VII.H. MTsN Model of Sungai Penuh in Jambi Province in listening the fable. The abim of this research was to describe the improvement of students’ ability at the class VII.H. MTsN Model of Sungai Penuh in listening carefully the fable by using audio media can be seen from five intrinsic elements, (plot, setting, character, theme and message). This research used theory of fable structure was said by Danandjaya. The type of this research was Class Action Research. Based on the data analysis, can be concluded that the improvement of student’s skill at at the class VII.H. MTsN Model of Sungai Penuh in listening carefully the fable by using audio media had already been good. (1) to be found that the improvement of students’ ability at the class VII.H. MTsN Model of Sungai Penuh in listening carefully the fable by using audio media at cycle I with the avarage value 72,06 to qualification was more than enough, (2) to be found that improvement of students’ ability at the class VII.H. MTsN Model of Sungai Penuh in listening carefully the fable by using audio media at cycle II with the avarage value 84,48 come to the exelent qualification. Thus, can be conluded that by using audio media, can be increase the students’ ability in listening the fable at at the class VII.H. MTsN Model of Sungai Penuh in Jambi Province.